PENGARUH METODE FIELD TRIP TERHADAP KEMAMPUAN MENULIS PUISI PADA SISWA SMA NEGERI 1 TORAJA UTARA - Rosi Singkali; Idawati Idawati; Azis Azis (Universitas Negeri Makassar, 2022)
The Effect of the Field Trip Method on the Ability to Write Poetry in Students of SMA Negeri 1 Toraja Utara. This research is an experimental study that aims to determine the effect of the field trip method on the ability to write poetry. The independent variable in this research is the field trip method, while the variable used is writing poetry text. The population in this study were all students majoring in science class X held 3 classes, while the sample was X IPA 3 with 36 students. The research data were obtained by giving pretest and posttest writing poetry texts. The data analysis technique is descriptive and inferential analysis using the IBM SPSS version 23 application. Based on the results of inferential statistical analysis, the comparison of the t-count and t-table values is 16,062> 1,68. Based on this, it is stated that the accepted hypothesis means that the field trip method has an effect on the poetry writing ability of the tenth graders of SMAN 1 Toraja Utara.